Non-destructive Technologies for Plant Health Diagnosis - Ang, Mervin Chun-Yi; Lew, Tedrick Thomas Salim (Frontiers in Plant Science, 2022)
As global population grows rapidly, global food supply is increasingly under strain. This is exacerbated by climate change and declining soil quality due to years of excessive fertilizer, pesticide and agrichemical usage. Sustainable agricultural practices need to be put in place to minimize destruction to the environment while at the same time, optimize crop growth and productivity. To do so, farmers will need to embrace precision agriculture, using novel sensors and analytical tools to guide their farm management decisions. In recent years, non-destructive or minimally invasive sensors for plant metabolites have emerged as important analytical tools for monitoring of plant signaling pathways and plant response to external conditions that are indicative of overall plant health in real-time. This will allow precise application of fertilizers and synthetic plant growth regulators to maximise growth, as well as timely intervention to minimise yield loss from plant stress. In this mini-review, we examine the in vivo electrochemical sensors and optical nanosensors that detect important endogenous metabolites within the plant, together with sensors that detect surface metabolites by probing the plant surface electrophysiology changes and air-borne volatile metabolites via chemical sensor arrays. The advantages and limitations of each kind of sensing tool are discussed with respect to their potential for application in high-tech future farms.